Generational Accounting Around the Globe - Kotlikoff, Laurence J; Raffelhüschen, Bernd (American Economic Review, 1999)
Generational accounting is a relatively new method of long-term fiscal planning and analysis. This paper presents a selection of the latest generational accounting results for 22 countries.